An Insight Into the Modulatory Effects and Mechanisms of Action of Phyllanthus Species and Their Bioactive Metabolites on the Immune System - Jantan, Ibrahim; Haque, Md. Areeful; Ilangkovan, Menaga; Arshad, Laiba (Frontiers in Pharmacology, 2019)
Phyllanthus species (family; Euphorbiaceae) have been one of the intensively studied plants for their immunomodulating effects due to their wide-ranging uses to treat immune-related diseases in indigenous medicine, and their ethnopharmacological usages are primarily with limited or lack of scientific basis. This review focuses on the significance of Phyllanthus species and their bioactive metabolites particularly phyllanthin, hypophyllanthin, niranthin, corilagin, geraniin, catechin, quercetin, gallic acid and ellagic acid in the regulation of both innate and adaptive arms of immune system through various mechanisms and their possible therapeutic benefits for treatment of immune related diseases. We have compiled all significant findings published in the literature and critically analyzed the data to provide perspectives and directions for future research for the plants as a prospective source of novel immunomodulators. Various Phyllanthus species particularly, P. amarus, P. emblica, P. niruri, and P. urinaria have been found to possess significant immunomodulatory effects. However, the possible challenges encountered by the application of extracts of various Phyllanthus species and their bioactive compounds as immunomodulators need to be addressed. Most of the studies were based on crude extracts of the plant. The compounds contributing to the bioactivities have not been properly identified, and mechanistic studies to understand the immunomodulatory effects of the plants are limited by many considerations with regard to design, conduct, and interpretation. Extensive experimental and preclinical studies on immunomodulating potential of Phyllanthus species should be carried out to provide sufficient data to prove that their traditional uses are inherently effective and safe, which will allow clinical trials to be pursued for their further development as therapeutic agents to treat immune-related disorders.